Identification of nonstandard macrocyclic peptide ligands through display screening. (December 2017) - Taylor, Rhys Dylan; Rey-Carrizo, Matias; Passioura, Toby; Suga, Hiroaki
Abstract : Techniques facilitating the synthesis and screening of very high diversity nonstandard macrocyclic peptide libraries have led to such compounds receiving increasing attention as potential drug candidates. Specifically, approaches which allow the use of non-proteinogenic amino acids are proving to be particularly effective, since they expand the accessible chemical space of the starting library and thus allow the identification of compounds with structural similarity to known drugs. This review focuses on mRNA display screening platforms for drug discovery and their combined use with genetic code reprogramming to identify novel macrocyclic peptides with high affinities for disease-related targets of interest.